DIPLOMASI EKONOMI INDONESIA TERHADAP KOREA SELATAN DALAM PERUNDINGAN INDONESIA KOREA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IK-CEPA) TAHUN 2014-2020 - Syafira Tasya Azzahra (2022)
This study discusses the problems of implementing Indonesia's economic diplomacy against South Korea in the 2014-2020 Indonesia Korea Comprehensive Economic Partnership Agreement (IK-CEPA) negotiations. The findings of the study indicate that the governments of Indonesia and South Korea agreed on the formation of the IK-CEPA, although the negotiation process experienced dynamics and had stalled. IK-CEPA is motivated by the government's efforts to improve Indonesia's economy with partner countries, create access to the formation of markets for Indonesian products to South Korea and investment from South Korea to Indonesia as well as to strengthen bilateral relations between the two countries. In the IK-CEPA negotiation process, dynamics began from the first round to the seventh round and the investment clause is still a pending issue. The IK-CEPA negotiations up to the seventh round experienced problems due to the lack of agreement on the entry of Indonesian products and the replacement of the presidents of the two countries in 2013 and 2014 so that they were suspended for five years. The Indonesian government carried out various strategies to reach an agreement after the assessment to continue the IK-CEPA negotiations agreed by the governments of the two countries in 2018.